Preferred event attributes, motives and satisfaction among sport tourists attending sepak takraw events in Malaysia - Zarei, Azadeh (2014)
Using Tourist Attraction System Model of Leiper (1990), this research has investigated demographic characteristics, event informational sources, sport event attributes, attendance motives, and satisfaction on sepak takraw sport event. A total of three hundred and sixteen (n=316) sport tourists comprised of domestic sport tourists (n=224) and foreign sport tourists (n=92) attending 2013 ISTAF Super Series were chosen as subjects. The demographic profiles’ results show differences in the following characteristics: marital status, nationality, ethnicity, last venue of attendance, income, and trip expenditure. With regard to markers, a great number of domestic sport tourists indicated using mass communication items and the word of mouth communication as the event information sources. However, social networking and mass communication were the most important sources of information for foreign sport tourists. The findings from MANOVA analysis show that there was a significant difference on the eight combined sport event attributes and the only dimension of sport facility among domestic and foreign sport tourists. Domestic and foreign sport tourists significantly differed in the eight combined attendance motives and the economic, aesthetic, family, and escape dimensions. The results from independent samples t-tests indicate that no significant difference was found in overall satisfaction between domestic and foreign sport tourists. These findings provided support for the sepak takraw sport event as a potential area of sustainable tourism development within small-scale sport-tourism context.